Spatio-temporal model to estimate life expectancy and to detect unusual trends at the local authority level in England. Issue 11 (12th November 2020) - Boulieri, Areti; Blangiardo, Marta
Abstract : Objectives: To estimate life expectancy at the local authority level and detect those areas that have a substantially low life expectancy after accounting for deprivation. Design: We used registration data from the Office for National Statistics on mortality and population in England, by local authority, age group and socioeconomic deprivation decile, for both men and women over the period 2001–2018. We used a statistical model within the Bayesian framework to produce robust mortality rates, which were then transformed to life expectancy estimates. A rule based on exceedance probabilities was used to detect local authorities characterised by a low life expectancy among areas with a similar deprivation level from 2012 onwards. Results: We confirmed previous findings showing differences in the life expectancy gap between the most and least deprived areas from 2012 to 2018. We found variations in life expectancy trends across local authorities, and we detected a number of those with a low life expectancy when compared with others of a similar deprivation level. Conclusions: There are factors other than deprivation that are responsible for low life expectancy in certain local authorities. Further investigation on the detected areas can help understand better the stalling of life expectancy which was observed from 2012 onwards and plan efficient public health policies.